Monitoring Fasilitas Pertamanan Kota Gorontalo Berbasis Sistem Informasi Geografis - Irma Surya Kumala Idris; Yasin Aril Mustofa (Jurnal Informatika Upgris, 2021)
City Park is part of the city's green open space, its existence has the meaning of securing natural ecosystems that have a great influence on the existence and survival of the city itself. The number of city parks in the city of Gorontalo also requires little cleaning and maintenance personnel. To find out the performance of officers in the field, we need a system that is able to monitor the results of the work, making it easier for the relevant offices to control the conditions, facilities and functions of the city park. This research is intended to build a geographic information system that will be used for monitoring park facilities equipped with related information that is easily accessible by the local government, especially the City Planning and Landscaping Office of Gorontalo City. This study uses the programming language PHP (PHP: Hypertext Preprocessor) and MySQL database, using descriptive methods, then implement this design to find out and measure the level of ease, speed of information, and accuracy of information. The results of the study based on the data obtained were then tested using the White Box Testing method and Bases Path Testing. From the data obtained then a flowgraph design was made. Flowgraph that is tested is the process of finding a location of a garden. From the results of the calculation of the White Box Testing and Bases Path Testing test methods, the results of the calculation results obtained that have met the requirements in terms of software feasibility. Based on the results of testing with the White Box Testing, and Base Path Testing method above, it can be concluded that true system logic can produce a system that is effective and efficiently logically, and is expected to facilitate the processing of said data.